Efeito da associação de vitamina D3 e curcumina nanoencapsuladas sobre a sinalização purinérgica em modelo de artrite - Silva, Jean Lucas Gutknecht da (2019)
Rheumatoid arthritis (RA) is a chronic, autoimmune, systemic inflammatory disease that is highly debilitating. Vitamin D3 (VD3) has an immunomodulatory role in RA, exerting an inhibitory action on T lymphocytes in the production and action of cytokines. Curcumin, a polyphenol derived from Curcuma longa, interacts with cellular and molecular targets, promoting pharmacological and immunomodulatory effects in many pathologies, including RA. Therefore, it is of scientific interest to test the therapeutic effects of these two substances combined. In order to increase the bioavailability and stability of curcumin and increase the therapeutic efficacy and bioactivity of the VD3 in the immune system, a nanoencapsulation system was used. Purinergic signaling plays a role in the modulation of inflammatory and immune responses of RA. Studies involving the evaluation of the activity of enzymes that participate in the degradation cascade of adenine nucleotides are important to verify the purinergic signaling in the regulation of the immune and inflammatory response during the clinical evolution of several diseases. The objective of this study was to evaluate the possible effects of the association of these compounds in the nanoencapsulated form on purinergic signaling by the activity of the enzymes E-ADA and E- NTPDase, in a model of arthritis induced by Freund's complete adjuvant (CFA). We also evaluated biochemical and oxidative stress parameters. Wistar rats were divided into groups with and without induction of arthritis. CFA was administered to the hind paw of the animals, after 15 days, arthritis induction, thermal hyperalgesia, paw edema, and arthritis score tests were performed. On the 15th day the treatment with VOC3 (15.84 IU / day) and curcumin 4mg / kg was started separately and in combination, or with curcumin in the free form 25mg / kg, with the vehicle or with white nanocapsules for 15 days. On the 30th day, arthritis induction, biochemical and ectoenzyme tests were performed on platelets, neutrophils, lymphocytes, myeloperoxidase (MPO) and reactive oxygen species (ROS). Liver and kidney were collected for histopathological analysis. The results demonstrate the success of the model in generating an inflammatory process, evidenced by the increase in paw edema and in the score of arthritis and hyperalgesia. No histopathological changes were observed in the hepatic analyzes of the animals and no deposition of nanocapsules was found. The increase in vascularization and disorganization of the renal glomeruli of the arthritic animals was reverted by the treatments. There was a reduction in E-NTPDase activity of neutrophils and an increase in E-ADA in neutrophils, platelets, and ADA in serum added with the decrease of E-ADA in lymphocytes suggest a proinflammatory response in induced animals. The high MPO activity in the arthritic animals confirmed the inflammatory process, however ROS levels did not change post induction and/or treatment. Both nanoencapsulated formulations have been shown to reduce the signs and symptoms of inflammation, revert changes in ectoenzyme activities, and protect liver and kidney tissues as seen in the histology and in the reduction of MPO activity. Thus, the treatments in association with nanocapsules were successful, suggesting an anti-inflammatory effect with reduction of the dose, and overcoming the difficulties of absorption and distribution of these compounds, and may serve as adjuvant therapy for the treatment of rheumatoid arthritis.